2021
DOI: 10.1111/apt.16358
|View full text |Cite
|
Sign up to set email alerts
|

Trends in paediatric inflammatory bowel disease‐attributable direct costs: a population‐based analysis

Abstract: SummaryBackgroundIn addition to its morbidities, inflammatory bowel disease (IBD) has a major financial burden on patients and healthcare systems. However, there is a paucity of evidence on IBD‐attributable costs in children.AimsTo determine the trends of IBD‐attributable direct costs over time using a population‐based analysis.MethodsData were extracted from Manitoba Health Provider Claims and other population registry datasets from 1995 to 2017. Children with IBD were matched by age, sex and location with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A Manitoba study reported significantly increasing total direct healthcare costs (including the costs of outpatient care, hospitalizations, surgeries, and medication) among people with IBD, from $3,354 per person per year in 2005 to $7,801 in 2015 (costs in 2015 CAD) ( 1 ). The increase in costs has been even greater for paediatric IBD, increasing from $1811 per person per year in 2004 to $14,792 per person per year in 2017 (costs in 2020 CAD); the cost of caring for children without IBD did not change over the course of the study ( 9 ). The average direct costs among children in Ontario diagnosed at <17 years of age between 2013 and 2019 was $14,451 (SD: 14,665) in the first year following diagnosis ( 29 ).…”
Section: Estimating the Total Direct Costs Of Ibd In Canadamentioning
confidence: 98%
See 2 more Smart Citations
“…A Manitoba study reported significantly increasing total direct healthcare costs (including the costs of outpatient care, hospitalizations, surgeries, and medication) among people with IBD, from $3,354 per person per year in 2005 to $7,801 in 2015 (costs in 2015 CAD) ( 1 ). The increase in costs has been even greater for paediatric IBD, increasing from $1811 per person per year in 2004 to $14,792 per person per year in 2017 (costs in 2020 CAD); the cost of caring for children without IBD did not change over the course of the study ( 9 ). The average direct costs among children in Ontario diagnosed at <17 years of age between 2013 and 2019 was $14,451 (SD: 14,665) in the first year following diagnosis ( 29 ).…”
Section: Estimating the Total Direct Costs Of Ibd In Canadamentioning
confidence: 98%
“…In these studies, hospitalization costs were averaged over all people with IBD, regardless of whether they were hospitalized. Costs of inpatient admissions for Manitoba children with IBD decreased from $365,252 in 2004 to $61,600 in 2017 ( P < 0.01); per-person hospitalization costs were not reported (costs in 2018 CAD) ( 9 ). The authors attributed this decrease in hospitalization costs to a reduction in IBD-related surgeries.…”
Section: Hospitalizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…OOP costs are those paid by the patients or their caregivers in cash or credit for healthcare related expenses that are not covered by the public health or insurance systems, such as disease‐related travel and parking costs, and costs of over‐the‐counter medications (1,2). In children and young adults with IBD, we recently demonstrated that the median annual direct costs per person were $1811 (Canadian dollars) in 2004 and significantly increased to $14,792 in 2017 (3). A recent report from Crohn’s & Colitis Canada showed that the direct cost of caring for people living with IBD in Canada in 2018 was estimated to be close to $1.28 billion and the total indirect and OOP costs were estimated to be $1.29 billion (4,5).…”
mentioning
confidence: 99%